Makna Semiotika Bacaan Doa dalam Tradisi Mattaro Ase Baru Masyarakat di Desa Mattampa Walie - Kurnia Kurnia; Andi Agussalim Aj; Aswati Asri (HUMAN: South Asian Journal of Social Studies, 2023)
Abstract. This study aims to describe the semiotic meaning of Prayer Reading in the Mattaro Ase Baru Tradition of the Community in Mattampa Walie Village, Lappariaja District, Bone Regency using Riffaterre's Semiotic Theory based on heuristic and hermeneutic readings. This research is a qualitative descriptive study. The data in this study is the reading of the new mattaro ase prayer 'save rice', with data sources from informants. Riffaterre's Semiotics Theory is used to describe the meaning of the text read only mattaro ase baru. Data analysis techniques found data reduction, data presentation and conclusions. The results of this study found five mantras in the process of storing rice, namely baca doang mappanessa esso, baca doang mala ase baru, baca doang maqbaca ase massio, baca doang maq rakkiyang, and baca doang massalamak ase, so as to produce the meaning contained in the text of the spell based on heuristic and hermeneutic readings. Keywords: Meaning, Baca Doang Mattaro Ase Baru, Riffaterre Semiotics, Heuristics, and Hermeneutics